PENGARUH POLITICAL CONNECTION, GENDER DIVERSITY, BOARD OF COMMISSIONERS DAN STATE OWNERSHIP TERHADAP TAX AGGRESSIVENESS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Wilbert; Jessy Safitri Sitorus; Khanti Listya (Journal Accounting International Mount Hope, 2024)
Companies are one of the taxpayers who have the opportunity to carry out tax avoidance because of the perception that high profits will be in line with the high tax burden that must be paid. This is the basis for companies to minimize tax burdens, which are then known as tax aggressiveness, in order to achieve net profit that is in accordance with company expectations. This study was conducted with the aim of determining the effect of political connection, gender diversity, board of commissioners and state ownership on tax aggressiveness in BUMN companies. The method used is quantitative with a total population of 24 companies and a sample of 14 companies, so that the total observation data obtained is 70. The data analysis technique used is multiple linear regression with SPSS version 25. The conclusions of this study are: 1) political connection does not affect tax aggressiveness, 2) gender diversity partially has a positive and significant effect on tax aggressiveness, 3) the board of commissioners partially has a negative and significant effect on tax aggressiveness, 4) state ownership partially does not affect tax aggressiveness, and 5) political connection, gender diversity, board of commissioners and state ownership simultaneously have a positive and significant effect on tax aggressiveness.